The effect of augmented reality on spatial visualization ability of elementary school student - Eh Phon, Danakorn Nincarean; Rahman, M. H. A.; Utama, N. I.; Ali, M. B.; Halim, N. D. A.; Kasim, S. (Insight Society, 2019)
The invention of Augmented Reality (AR) has provided a platform for individuals to see virtual and real objects simultaneously in a real-life setting. As compared to other technologies being implemented in education setting, it may contribute a new method to educate. This study investigated the possible effect of AR technology on students’ spatial visualization ability. AR-Science Magic Book Learning System (AR-SMB) is a learning tool based on the AR technology which was developed in this study to facilitate students in learning science concept, hence enhancing their spatial visualization ability. The type of data collection methodology used is the quantitative approach in which pre-test and post-test design were implemented and the participant comprised of 34 fifth-grade students. According to the results, it was found that the scores of the Mental Rotation Test (MRT) post-test were significantly greater than the pre-test, thus AR technology can be considered to be beneficial in enhancing students’ spatial visualization ability. There is a huge difference in terms of the scores of MRT between the pre-test and post-test which concludes that the treatment given can significantly improve and contribute towards their spatial visualization ability. The findings of this research enable the educators to incorporate AR learning into their teaching process in order for students to understand the rotation and transformation of objects that are related to each other. As a result, this study has shown a significant implication for the understanding of AR’s effect in enhancing spatial visualization ability among primary school students.